Communications cryptography - Khalifa, Othman Omran; Islam, Md. Rafiqul; Khan, Sheroz; Shebani, Mohammed S. (2004)
In today's information age, communications play an important role which 1s contributed to the growth o f technologies. Electronic security is increasingly involved in making communications more prevalent. Therefore, a mechanism is needed to assure the security and privacy o f information that is sent over the electronic communications media is in need. Whether the communications media is wired o r wireless, both can be not protected from unauthorized reception or interception of transmission. The, method of transforming the original information into the unreadable format is called encryption and decryption of information. The study o f encryption and decryption is known as Cryptography. Cryptography or communication by using secret code was used by the Egyptians some 4000 years ago. However, t h e science of cryptography was initiated by Arabs since 600s. Cryptography becomes vital in the twentieth century where it played a crucial role in the World War I and 11. This paper focuses on the analysis of the two types of key cryptography exists, based on the availability of the key publicly: Private key Cryptography, and Public Key Cryptography. Both the sender and the recipient share a key that must be kept private. In the former case the sender and recipient share a private key between the two o f them which must be distributed first before actual communications take place. This analysis shows how much complicated and difficult to do properly. T h e most famous example o f t h i s type of cryptography is the Data Encryption Standard (DES). In the Public Key Cryptography, each party has two sets o f keys; one key is known to the public while the other is kept secret to the owner.